A mesoscale analysis of relations between fish species richness and environmental and anthropogenic pressures in the Mediterranean Sea. (September 2022) - Carmezim, João; Pennino, Maria Grazia; Martínez-Minaya, Joaquín; Conesa, David; Coll, Marta
Abstract: Although there is a great knowledge about individual anthropogenic threats to different fish species in the Mediterranean Sea, little is known about how these threats accumulate and interact to affect fish species richness in conjunction with environmental dynamics. This study assesses the role of these threats in the fish richness component and identifies the main areas where the interaction between fish species richness and threats is highest. Our results show that fish richness seems to be higher in saltier and colder areas where the chlorophyll-a and phosphate concentrations are lower. Among the anthropogenic threats analyzed, the costal impact and the fishing effort seems to be the more relevant ones. Overall areas with high fish richness are mainly located along the western and northern shores, with lower values in the south-eastern regions. Areas of potential high cumulative threats are widespread in both the western and eastern basins, with fewer areas located in the south-eastern region. By describing the spatial patterns of the fish richness and which drivers explain these patterns we can also identify which anthropogenic activities can be managed more effectively to maintain and restore marine fish biodiversity in the basin. Highlights: A mesoscale spatial analysis of the Mediterranean fish species richness is performed. We assessed the role of anthropogenic and environmental variables on fish richness. Fish richness is higher in saltier, colder areas with lower chl-a and phosphate concentrations . Costal impact and the fishing effort are the most relevant anthropogenic threats. Areas with high fish richness are mainly located along the western and northern shores.